Hepcidin and iron status in chronic kidney disease - Toima, S; Madkour, M; Saleh, A; Hammam, O; Raafat, M (African Journal of Nephrology, 2010)
<span style="color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Hepcidin is a critical inhibitor of iron export frommacrophages, enterocytes, and hepatocytes. Given that itis filtered and degraded by the kidney, its elevated levelsin renal failure have been suggested to play a role in thedisordered iron metabolism of uremia. It is a smalldefensin-like peptide whose production by hepatocytes ismodulated in response to anemia, hypoxia, orinflammation. Hepcidin could also act as an indicator offunctional iron deficiency (FID) in chronic kidneydisease (CKD) patients. This study was performed toassess hepcidin and its correlations with renal function,iron status parameters {serum iron, serum ferritin,transferrin saturation (TSAT) and soluble transferrinreceptor (sTfR)}, inflammatory cytokines (IL-6&IFN-?)and inflammatory markers (CRP) in patients with CKDeither on conservative treatment or on maintenancehemodialysis (HD). Serum prohepcidin was higher inHD patients compared to controls and CKD patients. Inthe whole patient group, serum hepcidin correlatedsignificantly with hemoglobin (Hb), IL-6, creatinine,CRP, sTfR and urinary hepcidin. In HD groupprohepcidin correlated significantly with creatinine.Multiple regression analysis showed that prohepcidinwas most predicted by serum creatinine and CRP.Elevated prohepcidin levels in HD patients studied couldmainly be due to its accumulation in impaired renalfunction in addition to low-grade inflammation,frequently encountered in this population.